Arbuscular Mycorrhizal fungal strain dependant variation in root colonization spore population, growth promotion and yield response of Flue Cured Virginia tobacco (Nicotiana tabacum) - SUBHASHINI, D V; PADMAJA, K (The Indian Journal of Agricultural Sciences, 2014)
An experiment was conducted to evaluate the variability and performance of six AM fungi on plant growth promotion and phosphorus nutrition efficiency of FCV tobacco. Four species of Glomus and one species of Acaulospora were obtained from TERI and compared with native strain of Glomus sp. The VAM species were multiplied in situ on Zea mays. Later the inoculum was applied @ 40 spores/plant at the time of transplanting in RBD with untreated controls. Observations were recorded after 120 DAT. The results revealed that local isolate of Glomus spp significantly improved spore population and root colonization since early crop phenologies. The yield parameters were also significantly improved. Among TERI isolates G. intraradices performed at par with the local isolate. The definitive results suggest ample scope to utilize VAM in integrated nutrient management of tobacco.